Assessing primary educators’ needs for effective technology integration in English Language Instruction - Krishna Radi, Thamayanthi; Md Zabit, Mohd Nazir (Jurnal Pendidikan Bitara UPSI, 2025)
This study examines primary school English teachers' aspirations and challenges in using technology to improve English language instruction. These teachers represent a wide range of urban and rural teaching environments to shed light on their experiences and needs.  Cluster random selection was utilized to survey 252 primary school teachers in Kinta District, Ipoh, Perak, for a correlation quantitative research design. The study found that inadequate training, limited access to digital resources, and infrastructure constraints including low internet connectivity are major hurdles. Additionally, instructors stressed the importance of personalized learning programs for professional advancement. The main goal of such programs should be to give participants hands-on, practical training and continuing support to increase their confidence in using technology in the classroom. The study emphasizes the importance of aligning technological advances with pedagogical strategies to ensure their successful integration into teaching practices. This finding offers policymakers and educators realistic advice for equitable and effective technology use in English language training. These recommendations are presented by addressing the identified hurdles and providing support for teacher preparedness. The results of this study provide a technique to enhance the English language skills of elementary school pupils, making it possible for them to be better prepared to tackle the challenges of a digital and internationally connected life. This study contributes to the field of language education and educational technology by identifying targeted strategies to support English teachers in integrating digital tools effectively.